2021
DOI: 10.1016/j.dci.2021.104011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 17β-oestradiol on lymphopoiesis and immune system ontogenesis in juvenile sea bass, Dicentrarchus labrax

Abstract: The female sex steroid 17β-oestradiol (E2) is involved in the regulation of numerous physiological functions, including the immune system development and performance. The role of oestrogens during ontogenesis is, however, not well studied. In rodents and fish, thymus maturation appears to be oestrogen-dependent. Nevertheless, little is known about the function of oestrogen in immune system development. To further the understanding of the role of oestrogens in fish immune system ontogenesis, fingerlings of Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Furthermore, data from 120 dph time points revealed increased phagocytic activity of head kidney monocytes/macrophages. Moreira et al [ 106 ] reported that ER remained unchanged over the age and treatment comparisons, with the exceptions of Erβ and GPER. Both were modulated in younger cohorts and showed increased expression in the thymus of the older cohorts.…”
Section: Impact On Immune Systemmentioning
confidence: 99%
“…Furthermore, data from 120 dph time points revealed increased phagocytic activity of head kidney monocytes/macrophages. Moreira et al [ 106 ] reported that ER remained unchanged over the age and treatment comparisons, with the exceptions of Erβ and GPER. Both were modulated in younger cohorts and showed increased expression in the thymus of the older cohorts.…”
Section: Impact On Immune Systemmentioning
confidence: 99%